Importance of miR-141-5p and miR-501-5P expression in patients with HBV infection - Lak, Ramin; Yaghobi, Ramin; Garshasbi, Masoud (Cellular and Molecular Biology, 2021)
MicroRNAs (miRNAs) as small RNA and post-transcriptional modulators are shown to have regulatory effects for different cellular activities and pathways, such as metabolism, virus replication and also cell growth. In addition, miRNAs can regulate the replication of the hepatitis B virus (HBV). Therefore, the expression profile of miRNAs was evaluated in HBV-infected patient groups and healthy controls. The expression levels of the following microRNAs (as noninvasive biomarkers) were compared in two experimental (those with various stages of HBV infection) and control groups to evaluate their diagnosis ability: mir141-5p and mir501-5p. RNA extraction was performed for 45 serum samples. The miRCURY LNA™ Universal RT-miRNA-PCR system and miRNA PCR panels were used for measuring microRNA expression profiles. To normalize quantitative values, the endogenous reference by UniSp6 expression was used. Serum mir141-5p and mir501-5 were significant None in patient in different stages of HBV infection(p<0.001) than in controls(p<0.01). Receiver operating characteristic (ROC) curve analyses suggested that serum has mir141-5p and mir501-5p none significant diagnostic value for HBV infection. Results suggest that mir141-5p and mir501-5 can not be used as diagnostic biomarkers for monitoring of HBV infection and other biomarkers in this disease need to be investigated.